A Design and Build a Website for Catering Sales and Orders Using Web Engineering - Rd. Erwin Gunadhi, M.T.; M. Rikza Nasrulloh, M.Kom.; Epril Mohamad Rizaludin (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
Ordering catering is an activity carried out by consumers to order products in the form of food packages. At this time catering orders in the Garut area are still done manually, consumers see a list of products through brochures, even though consumers do not necessarily know the shape of the product written on the brochure, it will make it difficult for consumers to determine which product to choose, and these difficulties will making consumers have to meet with the owner of the catering frequently which will hinder time and drain costs. The existence of technology encourages researchers to build a catering ordering website which is expected to facilitate consumers in the catering ordering process. Consumers can find out the list as well as pictures of the products provided, with that consumers can easily determine which product to choose. Consumers can also save time and costs, because there is no need to repeatedly meet with the catering owner to find out the details of the products provided. The method used in the development of this application is the Web Engineering method with the stages of communication, planning, modeling, and deployment, using the php, html programming languages, using the Codeigniter framework and bootstrap and with MySql database management, by testing the Black Box Testing application.